Health Care Organization During Disasters - Akdeniz, Yonca Senem; Kıyak, Sevil Kuşku; İkizceli, İbrahim (Cerrahpaşa Medical Journal, 2023)
In recent years, both natural disasters and massive events have been increasing in our country as well as worldwide. During disasters, the health system, which routinely provides health care suddenly, loses its function. In case of any disaster or emergency, crisis management should be immediately initiated, and medical service delivery should be accordingly arranged. In such cases, instead of providing the utmost medical care to a single injured person, it is more vital to give the basic medical care to a maximum number of victims. In order for this to work, it is necessary to follow the prehospital and hospital triage principles. The preparations should be arranged in advance, the hospital disaster plan should be prepared, and practical training should be frequently done in certain periods for improving health care services in disasters. Cite this article as: Akdeniz YS, Kuşku Kıyak S, İkizceli İ. Health care organization during disasters. Cerrahpaşa Med J 2023;47(S1): 93-97